PERAN EKONOMI DIGITAL DALAM MENDORONG PERTUMBUHAN BISNIS DI INDONESIA: STUDI LITERATUR - Safitri, Camelia; Maya, Fasya; Hikmah, Mutiara; Indah, Nur (STIE Perbankan Indonesia, 2024)
Entering the Industrial Revolution 4.0, digital technology has become one of the main capital needed by industrial companies to develop their businesses. With the help of digital technology, a country can move its economy towards a digital economy. The development of the digital economy can give rise to new business models and play a role in encouraging business growth in Indonesia, integration between industries, and changes to existing industrial business models. This research is a literature review using qualitative methods. The data source used in this article is secondary data obtained from articles published in the last 10 years regarding the development of a sustainable digital economy in Indonesia. The digital economy was born and developed along with the increasingly globalized use of information and communication technology in the world. The wave of the digital economy has given birth to a smooth, inclusive and equal terrain. Factors that encourage business or entrepreneurial growth in Indonesia are increasing access to information and communication technology, increasing government support for entrepreneurship, growing entrepreneurial culture. The digital economy is an economic activity that utilizes digital technology and computers. The currently developing digital economy includes e-commerce and financial technology. The progress of the digital economy has provided business opportunities for business people, so worker skills must be a requirement to take advantage of the availability of technology in managing businesses to increase their income in their business ventures. Keywords: Economy, Digital, Business.